Fallen ebook A novel. - Slaughter, Karin (Will Trent, 2011)
NEW YORK TIMES BESTSELLER • “A complex, gripping, and deadly serious novel that reflects anew [Karin] Slaughter’s abundant talent.”— The Washington Post   WATCH WILL TRENT ON ABC • “An absolute master . . . Slaughter creates some wonderfully complex and mature female characters, a distinctive achievement in the world of thrillers.”— Chicago Tribune   “You know what we’re here for. Hand it over, and we’ll let her go.”   There’s no police training stronger than a cop’s instinct. Faith Mitchell’s mother isn’t answering her phone. Her front door is open. There’s a bloodstain above the knob. Her infant daughter is hidden in a shed behind the house. All that the Georgia Bureau of Investigations taught Faith Mitchell goes out the window when she charges into her mother’s house, gun drawn. She sees a man dead in the laundry room. She sees a hostage situation in the bedroom. What she doesn’t see is her mother. . . .   Faith is left with too many questions and not enough answers. To find her mother, she’ll need the help of her partner, Will Trent, and they’ll both need the help of trauma doctor Sara Linton. But Faith isn’t just a cop anymore—she’s a witness. She’s also a suspect.   The thin blue line hides police corruption, bribery, even murder. Faith will have to go up against the people she respects the most in order to find her mother and bring the truth to light—or bury it forever.